Physical and Mechanical Properties of the Muds of the Fergoug Dam - Benaissa, A.; Aloui, Z.; Ghembaza, M. S.; Trouzine, H.; Sebaibi, Y. (Engineering, Technology & Applied Science Research, 2014)
Volumes of dredged sediments are rather considerable and are estimated approximately 600 million m3 per year worldwide. These can represent a very interesting source of raw materials, in particular for a sector consuming aggregates such as civil engineering. The work presented in this article is interested particularly in the valorization of the muds which come from the dam of Fergoug (Algeria), with an aim of improving their mechanical behavior using binders (cement, lime) in order to use them in road engineering. To this end, we carried out a series of physical, chemical, mechanical and mineralogical analyses presented in this paper.